(3QSGdI GdRhQGAs - (3GdOhGfj , eMeO Hf GSYO GdUOjbj, LdGd GdOjf,J (B918 (3g` s
(3ChdgG (B:s
(3hHYO agPg fHPg ef GdMbGFb Hd RHOI ef GdObGFb efHg Yf GdTHjgGJ JegjO GdYdI ddTF HGdMbjbI eG jchf SHHkG dfaS Pdc GdTF s
(3BNQgG (B:s
( (3hCda eG ai jejfc Jdba eG UfYhG Ef eG UfYhG cjLO SGMQ hdG jadM GdSGMQ MjK CJi (B) (3hdGJfSfi ai ChbGJc hCTQcfi ai UhGdM OYhGJc hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B47s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B957s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs